Poland - The Functioning of the Labor, Land and Financial Markets : Opportunities and Constraints for Farming Sector Restructuring - World Bank (Washington, DC, 2013)
This study identifies several factors that inhibit efficiency improvements in the farming sector, both in themselves and through the dynamics of their mutual interaction. The study observes that incentives faced in the labor market have important implications for the land structure and, and in many ways, are at the heart of the problem of low labor productivity in agriculture. The study finds that, while rural households are increasingly diversifying their income sources out of farming, they have not moved away from rural areas because of the incentives to hold onto small agriculture plots and because of the high costs of formal employment outside agriculture. Instead, households have increasingly relied on so-called unearned income (pension benefits and other social transfers) and settled for informal employment in rural areas. This has done little to advance the social condition of rural households, or to improve agricultural productivity. This incentive to hold onto small agricultural plots, as well as other factors limiting the availability of land for commercial farming, has lead to an increasingly polarized land structure, with small farms becoming smaller, and large farms consolidating, albeit slowly.